Hubungan Masa Kerja dan Beban Kerja dengan Stres Kerja Perawat Pelaksana di RSUD ASA Depok Tahun 2024 - Yuliane Verantie; Indri Sarwili; Lannasari Lannasari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
High stress can have different effects on each person. Changes that arise due to work stress can change behavior and affect mental and physical health. In addition, stress in nurses also affects the quality of hospital services. The purpose of the study was to determine the relationship between work period and workload with work stress of implementing nurses at ASA Depok Hospital in 2024. This study is a quantitative type that is analytical in nature. The research design used is a cross-sectional study. The population in this study were all nurses at RSUD ASA Depok totaling 123 people. The determination of the sample in this study used a purposive sampling technique. The sample in this study was 94 respondents. In this study, the research instrument or tool used to collect data was by using a questionnaire. The researcher used the Chi Square test with a confidence level of 95% or a significance level of 5%. Based on the results of the study, there were more who had a work period of > 5 years, namely 53 respondents or 56.4%, more nurses felt a heavy workload, namely 59 respondents or 62.8% and more nurses felt moderate work stress, namely 36 respondents or 38.3%. The results of the statistical test of the relationship between length of service and work stress with a P value = 0.001 and the relationship between workload and work stress with a P value = 0.000. It is concluded that there is a relationship between work period and workload with work stress of implementing nurses at ASA Depok Hospital in 2024. Suggestions for Nursing Management including the head of the room to add personnel in each room so that it is not too heavy to work and for nurses to be able to apply good coping management in order to prevent work stress.